Resilience building against climate risks and impacts at community levels: A role for local financing mechanisms - International Institute of Rural Reconstruction; Cambodian Center for Study and Development in Agriculture (2020)
Climate events are expected to increase in both intensity and frequency: local risk financing strategies are important in any effort to build resilience including climate smart agriculture efforts. The Village Development Fund and Savings Group supported by the Biodiversity Corridors Project is one such effort that responds to communities at the front lines by providing financial protection against the impacts of climate-related shocks. Such strategies have enabled rural communities to better safeguard productive assets and income. These financing mechanisms, located close to where the community members live are better accessed by women borrowers with local financing institutions reporting better payment.